2019
DOI: 10.1371/journal.pone.0225548
|View full text |Cite
|
Sign up to set email alerts
|

Assessing service and treatment needs and barriers of youth who use illicit and non-medical prescription drugs in Northern Ontario, Canada

Abstract: BackgroundIllicit drug use rates are high among Canadian youth, and are particularly pronounced in Northern Ontario. The availability and accessibility of effective substance use-related treatments and services are required to address this problem, especially among rural and remote Northern communities. In order to assess specific service and treatment needs, as well as barriers and deterrents to accessing and utilizing services and treatments for youth who use illicit drugs in Northern Ontario, we conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…While familial and social influences can work to perpetuate the normalization of substance use, key informants indicated that they also may simultaneously play a large role in the stigmatization that deters youth from seeking support for problematic use. Stigma acts as a persistent barrier and creates additional challenges in ensuring youth are able to access critical services when they need them, and is particularly intensified for the adolescent age groups where parental engagement and consent in substance use treatment and services is often required [ 12 , 17 , 43 46 ]. Therefore, it is equally important to address stigma at various levels, including at the family and peer level since adolescents are highly engaged with and exposed to these groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While familial and social influences can work to perpetuate the normalization of substance use, key informants indicated that they also may simultaneously play a large role in the stigmatization that deters youth from seeking support for problematic use. Stigma acts as a persistent barrier and creates additional challenges in ensuring youth are able to access critical services when they need them, and is particularly intensified for the adolescent age groups where parental engagement and consent in substance use treatment and services is often required [ 12 , 17 , 43 46 ]. Therefore, it is equally important to address stigma at various levels, including at the family and peer level since adolescents are highly engaged with and exposed to these groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 9 ]. However, youth who do develop problematic substance use habits and related issues often experience inadequate access to primary mental health and substance use care due to multiple access barriers and scarcity of evidence-based services tailored for youth specifically [ 10 12 ]. In Ontario, a variety of youth-based services that address substance use exist, and youth receive care in multiple settings; however, the youth substance use service system overall has been characterized as fragmented, untimely, under-resourced and not user-friendly [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced by providers and patients: The barriers include competing time for providers’ limited practice time, preventing them from allocating enough time to properly evaluate patients’ risk of OUD/SUD, lack of interest in treating OUD/SUD, care fragmentation and distrust in the quality of care between PCPs and specialists, stigma surrounding the use of these treatments among patients and providers, provider’s stigma in dealing with OUD/SUD patients, being less receptive to patients’ treatment preferences (magnifying the importance of shared decision-making and physician-patient interaction), and nurses having low motivation/role support in working with patients [ 77 , 81 , 82 , 85 , 86 , 87 , 88 ]. Patients also deem transportation/mobility as a barrier in seeking treatments, especially in rural settings [ 88 ]. In addition, patients’ demographic and physiological characteristics (e.g., male gender, minority race, history of opioid overdose, and hepatitis C) are shown to be associated with a higher likelihood of abrupt discontinuation of treatments [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the 3 rd National Survey on Drug Use by the Brazilian Population, approximately 145 thousand adolescents aged 12 to 17 years were considered dependent on alcohol or some other substance, not including tobacco, and 38 thousand were considered to have been dependent on some illegal substance in the previous 12 months, with a mean age at first use of 13.1 years (Bastos, Vasconcellos, Boni, Reis, & Coutinho, 2017). International studies suggest that services that offer specific care for children and adolescents that use drugs, need to have a low threshold, provide 24-hours care and have empathic (non-critical) care providers, providing education on the benefits of treatment and involving the young people in the decision-making process (Dunne, Bishop, Avery, & Darcy, 2017;Russell et al, 2019).…”
mentioning
confidence: 99%